1984
DOI: 10.1016/0014-5793(84)80175-1
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR of intact muscle at 11 T

Abstract: 'H NMR spectra of intact frog, and chicken skeletal muscles, were recorded at 470 MHz with the Plateau and C&&on pulse sequence for the suppression of water [(1982) J. Am. Chem. Sot. 104, 73101. Only a few transients were required to resolve the resonances from the protons of muscle metabolites. The previously unobserved exchangeable protons of muscles were also recorded and thereby phosphocreatine and creatine could be measured simultaneously. During aging of dissected frog muscle, changes in levels of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 12 publications
5
36
0
Order By: Relevance
“…[23][24][25]), few have examined the quantification problem. Because of the need to suppress the intense Hz0 signal and to simplify the spectra, spinecho pulse sequences are used.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25]), few have examined the quantification problem. Because of the need to suppress the intense Hz0 signal and to simplify the spectra, spinecho pulse sequences are used.…”
Section: Discussionmentioning
confidence: 99%
“…W e attribute the doublets to 14~-13c dipolar coupling, which is not averaged to zero because the '% quadrupolar interaction is comparable in magnitude to the "N Zeeman interaction (53)(54)(55)(56). The magnitude of the apparent splitting is proportional to the dipolar interaction, ~~~~h / 4~r~( r~~) 3 , the quadrupolar interaction, e2qQ/ h, its orientation with respect to rm, and the magnitude of the Zeeman interaction, B,. No attempt will be made to analyze these line shapes at this time; details for related compounds are presented in refs.…”
Section: Solid I3c Spectrum Of Carnosinementioning
confidence: 99%
“…Various suggestions have been made (2) as to its role in living organisms but its precise function is not well understood. Carnosine has been the subject of numerous 'H and I3C nmr investigations, even being detected with 'H nmr in intact muscle (3)(4)(5). However, there still seems to be ambiguity over some of the proton and carbon-13 assignments.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have taken advantage of this pH sensitivity to measure the pH I of muscle in vivo and ex vivo (8 -13), and of muscle extracts (8,14). Specific applications have been made to muscle in resting (8,10,11,(13)(14)(15)(16), diseased (16), caffeinetreated (14), and exercised (9,11,12) states. Pan et al (11) and Hitzig et al (13) found high correlations between pH I measurements by the C-2 and P i methods.…”
mentioning
confidence: 99%